2002
DOI: 10.1096/fj.01-0765fje
|View full text |Cite
|
Sign up to set email alerts
|

β‐Carotene cleavage products induce oxidative stressin vitroby impairing mitochondrial respiration

Abstract: Carotenoids are widely used as important micronutrients in food. Furthermore, carotenoid supplementation has been used in the treatment of diseases associated with oxidative stress. However, in some clinical studies harmful effects have been observed, for example, a higher incidence of lung cancer in individuals exposed to extraordinary oxidative stress. The causal mechanisms are still unclear. Carotenoid cleavage products (CCPs), including highly reactive aldehydes and epoxides, are formed during oxidative at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 55 publications
4
74
0
1
Order By: Relevance
“…Related to our study, previous work showed that carotenoid cleavage products, such as highly reactive aldehydes and epoxides, cause oxidative stress by impairing mitochondrial function (52). Evidence is presented here that one mechanism of cell death induced by all-transretinal involves an intrinsic apoptotic pathway associated with mitochondrial impairment due to a rapid increase of intracellular calcium concentration (Figs.…”
Section: Abca4supporting
confidence: 77%
“…Related to our study, previous work showed that carotenoid cleavage products, such as highly reactive aldehydes and epoxides, cause oxidative stress by impairing mitochondrial function (52). Evidence is presented here that one mechanism of cell death induced by all-transretinal involves an intrinsic apoptotic pathway associated with mitochondrial impairment due to a rapid increase of intracellular calcium concentration (Figs.…”
Section: Abca4supporting
confidence: 77%
“…Being electrophilic, the α,β-unsaturated carbonyl group of β-CC and β-I can react with electron donors such as, for example, sulphydryl groups in proteins (15,16). Because of their reactivity, RES can be cytotoxic and, accordingly, a number of previous studies have reported the deleterious effect of high concentrations of β-carotene oxidation products, including β-I, on mitochondrial and chloroplastic functions, DNA intactness, and cell viability (25)(26)(27). In addition, low levels of RES, and particularly those produced during lipid peroxidation, have also effects on plant genome (19,28,29).…”
Section: Discussionmentioning
confidence: 99%
“…S3); and (iii) both retinoids and their condensation products are known to produce cellular toxicity and death (12,18,31,64,65). Retinal pathology could also result from mitochondrial dysfunction, because lipophilic unsaturated compounds such as retinoids can also act as electron acceptors that compromise ATP production (66)(67)(68)(69).…”
Section: Discussionmentioning
confidence: 99%